THE POSTCRANIAL SKELETON OF THE LOWER JURASSIC TRITYLODON LONGAEVUS FROM SOUTHERN AFRICA (Ameghiniana, 2017)
Tritylodon longaevus Owen, 1884 is one of the most common members of the Lower Jurassic faunas of the Karoo Basin. The cranial and dental anatomy of this taxon is well known, but its postcranium has not been previously addressed in detail. Our analysis shows that T. longaevus shares many postcranial features with other tritylodontids that distinguish them from other non-mammaliaform cynodonts. The correlation between taxon size and postcranial anatomical traits is briefly explored among tritylodontids, showing that few morphological differences among species correlate with size. Analysis of the purported oldest remains of Tritylodon, from the Norian Los Colorados Formation of Argentina, suggests that they cannot be unambiguously assigned to this taxon, circumscribing the record of Tritylodon to African localities. Resumen. EL ESQUELETO POSTCRANEANO DE TRITYLODON LONGAEVUS DEL JURÁSICO INFERIOR DE ÁFRICA DEL SUR. Tritylodon longaevus Owen, 1884 es uno de los taxones más comúnmente representados en las faunas del Jurásico Inferior de la Cuenca del Karoo. Este taxón es únicamente conocido a través de su anatomía craneana y dentaria mientras que su esqueleto postcraneano no ha sido previamente descripto en detalle. El presente estudio muestra que T. longaevus comparte con otros tritilodóntidos varios rasgos postcraneanos que los diferencian de otros cinodontes no mamaliaformes. También se explora aquí la correlación entre el tamaño corporal y a las variaciones en la anatomía postcraneana observadas en los tritilodóntidos, encontrándose que sólo unas pocas diferencias morfológicas entre especies se correlacionan con el tamaño. El re-análisis de los supuestos registros más antiguos (Noriano) de Tritylodon, procedentes de la Formación Los Colorados de Argentina, indica que estos restos no pueden asignarse sin ambigüedades a este taxón, circunscribiendo la distribución geográfica de Tritylodon a localidades de África.